THE RELATIONS BETWEEN CONCENTRATION OF NITRATE AND PHOSPHATE TO ABUNDANCE OF PLANKTONIC DIATOM IN SAKERA COAST WATERS OF BINTAN REGENCY OF KEPULAUAN RIAU PROVINCE - Nasution, Syafruddin; Ghalib, Musrifin; ', Maraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in February 2017 at Sakera coast Bintan regency of Kepulauan Riau Province,with the aims to determine the concentration of Nitrate and Phosphate in water, abundance of planktonic diatom and, the relationship between the concentration of Nitrate and Phosphate with abundance of planktonic diatom.The research methods used a was survey method. Each station consists of three sampling points. The results showed that the concentration of Nitrate ranged from 0.179-0.240 mg / L, whereas Phosphate concentration ranged from 0.175-0.194 mg/ L. The planktonic diatom found in the waters of Sakera coast consists of 2 ordo and 9 genus . The most dominant species were Isthmia sp, Chaetoceros sp and Nitzschia sp.The highest abundance was at station 4 which was a residential area (5540 ind /L), while the lowest was at station 1 which was the oil refining area (3488 ind / L). The relationship between concentration of Nitrate with diatom abundances has weak positive correlation, while the relationship between concentration of Phosphate with diatom abundances has weak negative correlation.Keywords : Coast Sakera, abundance, nitrate and phosphate, and diatoms